Dicing of viral replication intermediates during silencing of latent Drosophila viruses. - Flynt, A.; Liu, N.; Martin, R.; Lai, E.C. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Previous studies revealed roles for RNA interference (RNAi) in the immediate cellular response to viral infection in plants, nematodes and flies. However, little is known about how RNAi combats viruses during persistent or latent infections. Our analysis of small RNAs cloned from Drosophila cells latently infected with Flock House Virus (FHV) failed to reveal signatures of bulk degradation of the viral genome. Instead, this + strand virus specifically generated Dicer-2-dependent, 21-nucleotide siRNAs that derived in equal proportion from + and - strands. Curiously, luciferase reporters that are fully complementary to abundant viral siRNAs were poorly repressed. Moreover, although the viral siRNAs that were incorporated into an effector complex associated with Argonaute2, bulk FHV siRNAs in latently infected cells were not loaded into any Argonaute protein. Together, these data suggest that direct dicing of viral replication intermediates plays an important role in maintaining the latent viral state. In addition, the denial of bulk viral siRNAs from effector complexes suggests that criteria beyond the structural competency of RNA duplexes influence the assembly of functional silencing complexes.